2017
DOI: 10.1111/bph.13801
|View full text |Cite
|
Sign up to set email alerts
|

Biased agonism and allosteric modulation of G protein‐coupled receptor 183 – a 7TM receptor also known as Epstein–Barr virus‐induced gene 2

Abstract: Collectively, our data point to N114 as a key residue for EBI2 signalling controlling the balance between G protein-dependent and -independent pathways and facilitating sodium binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
3
12
0
1
Order By: Relevance
“…This receptor is predominantly cell surface−expressed and internalizes constitutively as well as ligand dependently (after addition of the endogenous agonist 7α,25‐dihydroxycholesterol (7α,25‐OHC)) . Consistent with a previous report, 23.5% of surface‐expressed GPR183 was constitutively internalized after 30 min (Fig. F), whereas the addition of 7α,25‐OHC enhanced the internalization to 43% (Fig.…”
Section: Resultssupporting
confidence: 90%
“…This receptor is predominantly cell surface−expressed and internalizes constitutively as well as ligand dependently (after addition of the endogenous agonist 7α,25‐dihydroxycholesterol (7α,25‐OHC)) . Consistent with a previous report, 23.5% of surface‐expressed GPR183 was constitutively internalized after 30 min (Fig. F), whereas the addition of 7α,25‐OHC enhanced the internalization to 43% (Fig.…”
Section: Resultssupporting
confidence: 90%
“…The recruitment of β-arrestin2 was measured using the PathHunter β-arrestin assay (DiscoverX) as described previously ( Daugvilaite et al, 2017 ). Briefy, cDNA encoding US28wt was fused to the ProLink C-terminal protein tag and the small fragment ofβ-galactose and cloned into pcDNA3.1+.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, for the b 2 -adrenoceptor, NMR studies have shown that "balanced" agonists for b 2 -adrenoceptors shift the ensemble equilibrium toward the G proteinspecific active state of helix 6 of the receptor, whereas b-arrestin-biased ligands regulate the conformational states in helix 7 . Similarly, bias SAR information regarding regions of receptors that are involved in biased signaling has also been obtained through site-directed mutagenesis as seen, for example, with G protein receptor 183 (Daugvilaite et al, 2017) and m-opioid receptors (Hothersall et al, 2017).…”
Section: Biased Receptor Signalingmentioning
confidence: 99%
“…For instance, the 5-HT 2A and b-adrenoceptor crystal structures have identified transmembrane domains specifically linked to biased ligand interaction (Warne et al, 2012;Wacker et al, 2013). Similarly, protein mutation has been employed to generate SAR data for biased signaling (G protein receptor 183, Daugvilaite et al, 2017;GLP-1, Wootten et al, 2016). Chemical scaffolds yielding biased molecules range from modification of natural endogenous agonists to natural products (Gupta et al, 2016).…”
Section: H Biased Signaling In Screening and Lead Optimizationmentioning
confidence: 99%
See 1 more Smart Citation